Sensitivity to antibiotics of Clostridium difficile toxigenic nosocomial strains - Beran, Vladimir; Chmelar, Dittmar; Vobejdova, Jana; Konigova, Adela; Nemec, Jakub; Tvrdik, Josef (Folia microbiologica, 2014)
Clostridium difficile is the etiological agent of diarrhoea and colitis, especially in elderly patients. The incidence of these diseases has increased during the last 10 years. Emergence of so-called hypervirulent strains is considered as one of the main factors responsible for the more severe disease and changed profile of sensitivity to antimicrobial agents. The aim of this work was to determine the sensitivity profile of toxigenic strains of C. difficile in the Czech Republic in 2011-2012 to selected antibiotics. The antibiotics clindamycin, metronidazole, vancomycin and amoxicillin with clavulanic acid were used for this purpose. Isolates cultured on Brazier's C. difficile selective agar were analysed for the presence of toxin genes using Xpert detection system. Xpert analysis revealed that 33 strains carried the genes for toxins tcdB, cdt and tcdCΔ117, thus showing characteristics typical for the hypervirulent ribotype 027/PFGE type NAP1/REA type B1. The remaining 29 strains carried only the gene for toxin B (tcdB) and not cdt and tcdCΔ117. Our results indicate the higher susceptibility of C. difficile hypertoxigenic strains to three out of four tested antibiotics (except vancomycin) than it is for the other toxigenic strains. We found that only 10.34% of other toxigenic strains were resistant to clindamycin, and no resistance was found in all other cases. All the isolates were sensitive to amoxicillin/clavulanic acid in vitro. However, its use is not recommended for therapy of infections caused by C. difficile.
Keywords: Bacterial Toxins; pseudomembranózní enterokolitida; Prohibitins; lidé; bakteriální léková rezistence; antibakteriální látky; Female; infekce spojené se zdravotní péčí; Clostridioides difficile; Humans; Anti-Bacterial Agents; prohibitiny; Microbial Sensitivity Tests; mikrobiální testy citlivosti; bakteriální toxiny; Cross Infection; Drug Resistance, Bacterial; mužské pohlaví; Enterocolitis, Pseudomembranous; ženské pohlaví; Male